Analisis terhadap Putusan Pengadilan Pajak Nomor PUT-015148.16/2020/PP/M.VIIIA Tahun 2025: Studi Kasus Sengketa Pajak Pertambahan Nilai atas PT Hina Motors Sales Indonesia - Lena Al; Ida Farida Adi Prawira; Rika Nurrizkiana (Jurnal Akuntansi, Perpajakan dan Auditing, 2025)
This study aims to analyze the legal basis and judicial considerations in Tax Court Decision No. PUT-015148.16/2020/PP/M.VIIIA of 2025 concerning a Value Added Tax dispute between PT Hino Motors Sales Indonesia and the Directorate General of Taxes. The research employs a normative juridical approach with qualitative analysis of legal documents and tax regulations. The results show that the Tax Court found the Directorate General of Taxes failed to fully uphold the principles of legal certainty, fairness, and transparency during the tax audit. Several tax corrections were deemed invalid due to lack of evidence, while minor ones remained payable. This decision emphasizes the importance of applying the rule of law in taxation and strengthens the Tax Court’s role as a guardian of fiscal justice in Indonesia.